It is your fault! How blame attributions of breach predict employees’ reactions - Costa, S.; Neves, P. (Journal of Managerial Psychology, 2017)
Purpose: Using insights from attributions, planned behavior, and fairness theories, this study examines the effect of blame attributions of psychological contract breach on employees’ attitudes (affective organizational commitment) and behaviors (organizational citizenship behavior (OCB)). The purpose of this paper is to understand whether employees’ reactions depend on the attributions they make concerning who is responsible for the breach. Design/methodology/approach: Cross-lagged design in which data were collected from 220 employees and their supervisors in a public company at two times. Moderated mediation was tested using the bootstrapping analysis outlined by Hayes (2012). Findings: The results supported the authors’ predictions: employees’ blame attributions to the organization have a negative impact on OCBs (as rated by supervisors in time 2) through decreased affective organizational commitment, but blame attributions to the economic context act as a buffer to the relationship between blame attributions to organization and affective organizational commitment, with consequences for OCBs. Research limitations/implications: Attributions can also be made to concrete persons (i.e. supervisor, coworker, self) rather than to just the organization or context. Practical implications: When hiring, recruiters should provide accurate and realistic promises to the candidates. When facing hard times, managers should provide additional information to employees and adjust their expectations to the current situation of the firm. Originality/value: This study makes a unique contribution to the literature by questioning the “single story” perspective about reactions to psychological contract breach, in which it is assumed that employees always respond negatively to such event.